Hrm, ethics and the other: a re-thinking of managing workforce diversity in post-war sri lanka - Jayawardena, D. (University of Jaffna, 2012)
New socio-economic space emerged in post-war work organizations in Sri Lanka, it is argued, is promising in promoting and managing workforce diversity. Yet, it is suspicious whether the phenomenon of HRM, being the officially recognized apparatus of managing diversity as well as employment in work organizations, is in a position to accommodate this emerging reality in post-war work organizations in Sri Lanka since the phenomenon, as literature suggests, is keen to overlook the presence of the other in the work milieu. Nevertheless, HRM’s denial in recognizing the other as other not only creates a doubt about the phenomenon’s ability of managing workforce diversity. It also raises the question of ethics in HRM. This paper critically explores ethics in HRM vis-à-vis managing workforce diversity in post-war work organizations in Sri Lanka. This paper examines how the phenomenon of HRM, chiefly via its language, has portrayed men and women in contemporary work organizations as a “new” subject – human resource. This subjectification process – through which one becomes a subject– as this study dissects it, is, however, unable to recognize diversity among men and women in the work milieu. Instead it objectifies individual subjects and thus denies the presence of the other as other. This denial of other’s presence, as it explicates, also always tends to dehumanize men and women in post-war work organizations in Sri Lanka. In this context this paper concludes by arguing that the phenomenon of HRM creates an indissoluble ethical paradox within which individual subjects become objects of management, if not objectified subjectsNew socio-economic space emerged in post-war work organizations in Sri Lanka, it is argued, is promising in promoting and managing workforce diversity. Yet, it is suspicious whether the phenomenon of HRM, being the officially recognized apparatus of managing diversity as well as employment in work organizations, is in a position to accommodate this emerging reality in post-war work organizations in Sri Lanka since the phenomenon, as literature suggests, is keen to overlook the presence of the other in the work milieu. Nevertheless, HRM’s denial in recognizing the other as other not only creates a doubt about the phenomenon’s ability of managing workforce diversity. It also raises the question of ethics in HRM. This paper critically explores ethics in HRM vis-à-vis managing workforce diversity in post-war work organizations in Sri Lanka. This paper examines how the phenomenon of HRM, chiefly via its language, has portrayed men and women in contemporary work organizations as a “new” subject – human resource. This subjectification process – through which one becomes a subject– as this study dissects it, is, however, unable to recognize diversity among men and women in the work milieu. Instead it objectifies individual subjects and thus denies the presence of the other as other. This denial of other’s presence, as it explicates, also always tends to dehumanize men and women in post-war work organizations in Sri Lanka. In this context this paper concludes by arguing that the phenomenon of HRM creates an indissoluble ethical paradox within which individual subjects become objects of management, if not objectified subjects